The impact of the World Health Organization Health Promoting Schools framework approach on diet and physical activity behaviours of adolescents in secondary schools: a systematic review. (May 2020) - McHugh, C.; Hurst, A.; Bethel, A.; Lloyd, J.; Logan, S.; Wyatt, K.
Abstract: Objective: To examine the effectiveness of interventions using the World Health Organization Health Promoting Schools (HPSs) framework approach in increasing physical activity (PA) and improving the diet of 11–18-year-olds. Study design: A systematic review guided by the National Health Services Centre for Reviews and Dissemination framework and reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses. Methods: Nine databases and trial registries were searched from 2013 to 2018 for cluster randomised controlled trials involving adolescents' aged 11–18 years. We also included relevant studies from a 2014 Cochrane Review of HPS approach on health behaviours. Data were extracted from included studies and assessed for quality. Results: Twelve eligible studies were identified from seven countries. The studies varied in outcome measures, sample size, quality and duration of intervention and follow-up. Only four of the included studies were of high to moderate quality. We found some evidence of effectiveness for physical activity only interventions and limited evidence of effectiveness for nutrition only and combined PA and nutrition interventions. Conclusions: There were no discernible patterns across the studies to suggest effective mechanisms for the HPS approach. The family/community component was poorly developed and superficially reported in all studies. Future research should seek to understand how best to work in partnership with secondary schools, to foster and sustain a healthy eating and physical activity culture, which aligns with their core aims. More attention should be paid to the restriction of unhealthy foods in the school environment. Highlights: Lack of high quality studies in adolescents, particularly in 16–18-year-olds. World Health Organization Health Promoting Schools (HPSs) framework needs to be reconceptualised for secondary schools. Development, delivery and evaluation of HPS components needs improvement. Restricting unhealthy food options shows promise.